2009
DOI: 10.1158/0008-5472.can-09-1075
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Multidrug Resistance–Associated Protein 1 Inhibitor Reversan Increases the Therapeutic Index of Chemotherapy in Mouse Models of Neuroblastoma

Abstract: The multidrug resistance-associated protein 1 (MRP1) has been closely linked to poor treatment response in several cancers, most notably neuroblastoma. Homozygous deletion of the MRP1 gene in primary murine neuroblastoma tumors resulted in increased sensitivity to MRP1 substrate drugs (vincristine, etoposide, and doxorubicin) compared with tumors containing both copies of wild-type MRP1, indicating that MRP1 plays a significant role in the drug resistance in this tumor type and defining this multidrug transpor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 32 publications
7
105
1
2
Order By: Relevance
“…At 1 day after 4T1 cell injection, the mice were injected with 100 L of the chemotherapy drug by intraperitoneal injection, as described previously. 23 For each model, chemotherapy treatment of BALB/c mice was randomized into five groups of five mice each. The control group was injected with 0.9% saline.…”
Section: Animal Model and Drug Treatmentmentioning
confidence: 99%
“…At 1 day after 4T1 cell injection, the mice were injected with 100 L of the chemotherapy drug by intraperitoneal injection, as described previously. 23 For each model, chemotherapy treatment of BALB/c mice was randomized into five groups of five mice each. The control group was injected with 0.9% saline.…”
Section: Animal Model and Drug Treatmentmentioning
confidence: 99%
“…However, when evaluating this possibility the following points should be considered. First, imatinib is not a substrate for MRP1 [46] which in clinical settings [45] and in animal models [47] has been demonstrated to be a key factor for multidrug resistance in neuroblastoma. Second, although imatinib is a substrate of MDR1, the reported IC 50 of imatinib for MDR1 (3-8 mM) [48] is 1-2 log greater than the IC 50 of imatinib for its high affinity targets.…”
Section: Discussionmentioning
confidence: 99%
“…This cross yielded murine neuroblastoma tumours that were either wild-type (MRP1 +/+ ) or homozygous null (MRP1 −/− ) for MRP1. Tumour cells of either MRP1 genotype were isolated and xenografted into nude mice and these mice were treated with clinically used drugs and monitored for tumour growth (Burkhart, Watt et al, 2009). Results showed that loss of MRP1 significantly increased the latency of tumour progression in response to vincristine and etoposide, both of which are known MRP1 substrates.…”
Section: Rationale For Targeting Mrp1mentioning
confidence: 99%